Theorizing Sex Differences in Political Knowledge: Insights from a Twin Study. Issue 1 (March 2014) - Hannagan, Rebecca J.; Littvay, Levente; Popa, Sebastian Adrian
<x content-type="archive" xml:space="preserve">Abstract</x> It is well established that women and men differ in their psychological orientation to politics (Burns, Schlozman, and Verba 2001; Dolan 2011; Fox and Lawless 2004; Thomas 2012). In addition to willingness to run for office, expressing interest in politics, and political efficacy, men and women tend to differ in reporting their factual knowledge of politics, but how do we explain the gap? This question is not merely important from a measurement standpoint (e.g., Mondak and Anderson 2004) but also has implications for our understanding of gendered political attitudes and behaviors. The gap can be reduced when controlling for a number of factors, but there remains a residual when measuring knowledge with the scale most widely used. This paper aims at providing insight on how we think not only about measuring something like "political knowledge" but also how we theorize gendered political behavior. We present a behavioral genetic analysis of sex differences in political knowledge using a genetically informative twin design to parse out the source of variation in knowledge. We do so predicated on a framework for thinking about gendered patterns in political behavior as well as findings from the existing literature on gender differences in the psychological orientation to politics. We believe our findings give us insight on what is wrong with current and seemingly gender-neutral measures of political knowledge.